2017
DOI: 10.1002/rcm.7839
|View full text |Cite
|
Sign up to set email alerts
|

Optimization by infusion of multiple reaction monitoring transitions for sensitive quantification of peptides by liquid chromatography/mass spectrometry

Abstract: Isotopically labelled peptides can be used to optimize MRM transitions more efficiently in FIA than by searching databases. The MRMOptimizer software is MS independent and enables the post-acquisition selection of MRM parameters. Coefficients of variation for optimal CE values are lower than those obtained with the SRMAtlas approach (B2) and one additional peptide was detected. Copyright © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…oxyphylla extract and provided the best resolution of oxyphylla A enantiomers. Some studies have demonstrated that the combination of chiral LC and MRM with a high degree of specificity and sensitivity is more appropriate for the identification and quantification of enantiomers . Therefore, a chiral HPLC–MRM–MS method was employed to separate and determine oxyphylla A enantiomers in A.…”
Section: Resultsmentioning
confidence: 99%
“…oxyphylla extract and provided the best resolution of oxyphylla A enantiomers. Some studies have demonstrated that the combination of chiral LC and MRM with a high degree of specificity and sensitivity is more appropriate for the identification and quantification of enantiomers . Therefore, a chiral HPLC–MRM–MS method was employed to separate and determine oxyphylla A enantiomers in A.…”
Section: Resultsmentioning
confidence: 99%
“…Skyline software 10 is extensively popular for quantitative proteomics, because it suggests quantitative precursor‐to‐product ion transitions along with OCE for the peptides of interest. This versatile tool empirically considers that OCEs are positively, linearly correlated with HR‐ m/z values of the precursor ions when precursor ions are compared with identical charging states.…”
Section: Figurementioning
confidence: 99%
“…For proteins that are not present in repositories, bioinformatic tools can be used to provide potential proteotypic peptides. Also, assistance for predictions for optimal transitions and corresponding CE values from initial measurements can be obtained (Alghanem et al, 2017; Colangelo et al, 2013; Pino, Searle, et al, 2020; Vidova & Spacil, 2017). Labeling techniques can also be combined with MRM quantification methods.…”
Section: Use Case Studiesmentioning
confidence: 99%